2015
DOI: 10.1177/1354068815601787
|View full text |Cite
|
Sign up to set email alerts
|

Contagious Euroscepticism

Abstract: This article examines whether the support for Eurosceptic challenger parties influences mainstream party position change on European integration in Western Europe. The key finding is that Eurosceptic challenger support is capable of influencing mainstream position shifts on European integration provided that, on average, EU issues are regarded as important by the Eurosceptic challengers. Moreover, the centre-left is more affected by Eurosceptic contagion since it is influenced by both radical right and radical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
51
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(60 citation statements)
references
References 59 publications
4
51
0
1
Order By: Relevance
“…Moreover, the finding that the radical left was not able to mobilize significantly more resonates well with the view that cultural aspects of European integration have become more pervasive than socio-economic conflicts (Hooghe & Marks, 2009;Meijers, 2015).…”
supporting
confidence: 53%
See 3 more Smart Citations
“…Moreover, the finding that the radical left was not able to mobilize significantly more resonates well with the view that cultural aspects of European integration have become more pervasive than socio-economic conflicts (Hooghe & Marks, 2009;Meijers, 2015).…”
supporting
confidence: 53%
“…The radical right rejects the EU on the basis of identity and sovereignty concerns, while the radical left rejects the EU on the basis of its ingrained marketliberal policies (de Vries & Edwards, 2009). In line with arguments that party competition over cultural issues is becoming more salient (Hooghe & Marks, 2009;Kriesi, 2007), Meijers (2015) has shown that the 'contagion effect' of Eurosceptic success was stronger for the radical right than for the radical left. The radical right's cultural arguments against Europe do not only influence the centre-right, but can also provoke accommodative reactions from the centre-left parties (cf.…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…Anti-European political sentiments could force mainstream parties to take more careful positions in EU negotiations in an attempt to court moderately anti-European voters at home. There is some evidence to suggest that fringe parties have already contributed to a shift in the political agendas for governing parties in core member states (Meijers 2015).…”
Section: Driver 2: European Capacity For Collective Actionmentioning
confidence: 99%